Assessing socioeconomic status in adolescents: the validity of a home affluence scale. Issue 8 (1st August 2002) - Wardle, J; Robb, K; Johnson, F
Abstract : Study objective: To examine the completion rate, internal reliability, and external validity of a home affluence scale based on adolescents' reports of material circumstances in the home as a measure of family socioeconomic status. Design: Cross sectional survey. Setting: Data were collected from a school based study in seven schools in the north of England Cheshire over a five month period from September 1999 to January 2000. Participants: 1824 students (1248 girls, 567 boys) aged 13–15 years who were attending normal classes in Years 9 and 10 in 7 schools on the days of data collection. Main results: Comparatively poor completion rates were found for questions on parental education and occupation while material deprivation items had much higher completion rates. There was evidence that students with poorer material circumstances were less able to report parental education and occupation whereas material based questions showed less bias. A home affluence scale composed of material items was found to have adequate internal reliability and good external validity. Conclusions: A home affluence scale based on material markers provides a useful alternative in assessing family affluence in adolescents. Additionally, it prevents exclusion of those less materially well off adolescents who fail to complete conventional socioeconomic status items.